Analysis of soils by means of Pfeiffer's circular chromatography test and comparison to chemical analysis results. Issue 3 (3rd July 2017) - Kokornaczyk, Maria Olga; Primavera, Fabio; Luneia, Roberto; Baumgartner, Stephan; Betti, Lucietta
Abstract: Pfeiffer's circular chromatography (PCC) is an analytical method relying on paper chromatography principles and applied mainly to test the quality of soils. The output of PCC are colored patterns formed on circular filter papers, pretreated with a photosensitive substance, and imbibed with a NaOH aqueous extract of the soil sample. In this study ( performed in frames of the project 'Panis cum Carne' financed by the Umbria Region, Italy) 16 soil samples from differently managed fields and planted with different crops were analysed by means of PCC and standard chemical analysis. The PCC pattern evaluation consisted of three approaches: (i) measurement of pattern zones, (ii) visual scoring of pattern characteristics by schooled evaluators, and (iii) computerised texture analysis. Subsequently the collected PCC data were correlated with the chemical soil characteristics; there were strong significant correlations with the contents of organic matter, total nitrogen, and assimilable phosphorus and bromine. The results of this study provide evidence that PCC patterns may provide an overall and reliable view on the soil state.